2000
DOI: 10.1128/aac.44.9.2498-2502.2000
|View full text |Cite|
|
Sign up to set email alerts
|

In Vitro Antiproliferative Effects and Mechanism of Action of the New Triazole Derivative UR-9825 against the Protozoan ParasiteTrypanosoma(Schizotrypanum)cruzi

Abstract: We describe the in vitro antiproliferative effects of the new triazole derivative UR-9825 against the protozoan parasite Trypanosoma (Schizotrypanum) cruzi, the causative agent of Chagas' disease in Latin America. The compound was found to be extremely active against the cultured (epimastigote) form of the parasite, equivalent to that present in the reduviid vector, with a MIC of 30 nM, a concentration 33-fold lower than that required with the reference compound ketoconazole. At that MIC, growth arrest coincid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(27 citation statements)
references
References 37 publications
0
25
0
2
Order By: Relevance
“…1), such as TAK-187 (Takeda Chemical Company) (Urbina et al 2003c, Corrales et al 2005, UR-9825 (Uriach & Company) (Urbina et al 2000, Guedes et al 2004) and ravuconazole (ER-30346, Eisai Co.; BMS 207,147; Bristol-Myers Squibb) (Urbina et al 2003b) also exhibit trypanocidal activity in vitro and in vivo. TAK-187 is a long-lasting triazole derivative with broad-spectrum antifungal activity, which also possesses very potent anti-T. cruzi activity in vitro and is capable of curing both acute and chronic infections in murine hosts even when the infecting strain is resistant to nitrofuran and nitroimidazole (Urbina et al 2003c).…”
Section: Ergosterol Biosynthesis Inhibitors (Ebi) As Potential New Thmentioning
confidence: 99%
See 1 more Smart Citation
“…1), such as TAK-187 (Takeda Chemical Company) (Urbina et al 2003c, Corrales et al 2005, UR-9825 (Uriach & Company) (Urbina et al 2000, Guedes et al 2004) and ravuconazole (ER-30346, Eisai Co.; BMS 207,147; Bristol-Myers Squibb) (Urbina et al 2003b) also exhibit trypanocidal activity in vitro and in vivo. TAK-187 is a long-lasting triazole derivative with broad-spectrum antifungal activity, which also possesses very potent anti-T. cruzi activity in vitro and is capable of curing both acute and chronic infections in murine hosts even when the infecting strain is resistant to nitrofuran and nitroimidazole (Urbina et al 2003c).…”
Section: Ergosterol Biosynthesis Inhibitors (Ebi) As Potential New Thmentioning
confidence: 99%
“…More recent work has shown that this compound is superior to BZN in preventing cardiac damage in a murine Chagas disease model (Corrales et al 2005). UR-9825 is another potent fungal and protozoan CYP51 inhibitor with remarkable in vitro anti-T. cruzi activity (Urbina et al 2000). However, its very short half-life in the mouse (< 0.5 h) precluded in vivo studies in this animal model, but work in a canine model has demonstrated that the compound exhibits curative activity against established infections of the virulent Y strain of T. cruzi with very low toxicity, although drug resistance was encountered with the Berenice-78 strain (Guedes et al 2004).…”
Section: Ergosterol Biosynthesis Inhibitors (Ebi) As Potential New Thmentioning
confidence: 99%
“…Among these are allopurinol, an antiuricemic hypoxanthine that is used to treat gout, and antifungals that inhibit ergosterol, such as ketoconazole, itraconazole and fluconazole [42][43][44][45][46] . These have not been shown to be effective in vivo, including during the acute phase of the disease.…”
Section: Drugs In Use and New Strategies For Treating Chagas Diseasementioning
confidence: 99%
“…1) displays in vitro activities against T. cruzi comparable to those of the most potent EBIs tested against this organism, and detailed biochemical studies indicated that its mechanism of action is due to a specific interference of the parasite's sterol C-14␣-demethylase (29). However, in vivo efficacy against T. cruzi requires both potent intrinsic antiparasitic activities and special pharmacokinetic properties (long terminal half-lives and large volumes of distribution) (28,33).…”
mentioning
confidence: 99%